Increased reporting of subjective cognitive complaints over time predicts cognitive decline and incident dementia. (6th July 2021) - Numbers, Katya; Lam, Ben C. P.; Crawford, John D.; Kochan, Nicole A.; Sachdev, Perminder S.; Brodaty, Henry
Abstract: Background: Subjective cognitive complaints (SCCs) are a risk factor for dementia; however, little is known about their trajectories. Method: Participants were 873 older adults (mage = 78.65 years; 55% females) from the Sydney Memory and Ageing Study that were followed‐up biennially. SCCs were measured using the six‐item Memory Complaint Questionnaire. Associations between initial level of SCC reporting, linear change in SCC reporting, and change in global cognition over 6 years was examined using latent growth curve analysis. Risk of dementia was examined over 10 years using Cox regression. Results: After controlling for demographics, mood and personality, results revealed a negative longitudinal association between the slope of SCCs and the slope of global cognition scores ( b  = −0.01, p  = 0.005, β  = −0.44), such that participants who reported increasing SCCs showed a steeper rate of decline in global cognition over 6 years. Cox regression also revealed participants who reported increasing SCCs had a nearly fourfold increased risk of developing dementia over 10 years (hazard ratio 3.70, 1.24–11.01). Conclusion: This study explored whether initial levels of, and change in, SCCs over time are associated with both cognitive decline and risk of dementia. These findings are clinically relevant as GPs should note patients reporting increasing SCCs as they may be at greater risk of cognitive decline and incident dementia. Highlights: Existing longitudinal data on the association between subjective cognitive complaints (SCCs) and cognitive outcomes over time has focused on associations with decline in memory or other cognitive domains, or on associations with risk of incident dementia, but not both. To our knowledge, no study has examined whether changes in SCCs reporting predict both cognitive decline and incident dementia in the same cohort. Controlling for mood and personality, participants who reported increasing SCCs showed a steeper rate of cognitive decline over 6 years and had a nearly fourfold increased risk of dementia over 10 years. Examining longitudinal features of SCCs provides novel and important insight into their association with underlying cognitive changes. GPs and Clinicians should note patients reporting increasing SCCs over time as this is associated with future cognitive decline and risk of dementia.